Genetic investigation on the pathophysiology and clinical symptoms of Hereditary Angioedema (Research, Society and Development, 2020)
Hereditary Angioedema (HAE) is a disorder unknown by many health professionals, thus being underdiagnosed. The objective of the study was to analyze the articles related to the topic addressed in the last 5 years. HAE is a rare and severe genetic disease of the immune system, caused by a deficiency of the C1 esterase inhibitor (C1-INH), presenting an autosomal dominant inheritance. It is classified into 3 phenotypes: quantitative deficiency of the C1-INH inhibitor, dysfunction of the C1-INH and normal C1-INH. Mutations in several genes are associated with the HAE phenotype; patients with deficiency and dysfunction of the C1-INH protein have mutations in the SERPING1 gene, and patients with normal C1-INH may present mutations in the following genes: F12, angiopoietin (ANGPT1), plasminogen (PLG) or kininogen (KNG1). The symptoms of HAE include recurrent edema in several body parts, both on the skin and on internal organs. For the preparation of this study an integrative literature review was carried out, the articles were searched in three electronic databases (Google Scholar, PubMed and Scielo) using the descriptors “hereditary angioedema”, “mutations”, “bradykinin”, “C1-INH”, “SERPING1”, “plasminogen”, “angiopoietin”, “F12” and “kininogen”, connected by Boolean operators AND and OR. We found a a total of 874 articles, and after the screening, 32 articles were evaluated. This research enabled the understanding not only of the precursor mechanisms that leads to the development of this disease, but also of the genetic mutations responsible for the variety of HAE’s clinical manifestations, corroborating the building of knowledge of professionals involved in the diagnosis and treatment of this disorder.